The Effectiveness of Word Wall Media on Students' Vocabulary Mastery - Reviana, Syefti Swensi Olovia; Erni, Erni; Aruan, Rumiri Rotua (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The purpose of this study was to investigate the effects of word wall media on students' vocabulary mastery in the seventh grade of SMPN 8 Rupat. The research applied a quasi-experimental design, with two classes as the experimental and control groups. This study used a one-equivalent control group design (pre-test and post-test). The samples for this research were 36 students in VII-1 and VII-2 classes. According to the result, the average for the pre-test was 33.42, while the average for the post-test was 76.15. For more details, a paired T-test was conducted on the students' pre-test and post-test scores. The results revealed that students taught with Word Wall media showed improved vocabulary mastery compared to their counterparts because the sig. (2-tailed) value following the paired sample T-test is 0.000, which is smaller than 0.05.